Linear and non-linear regression model fitting of testicular three-dimensional growth in Miranda donkeys. Issue 1 (1st January 2021) - Martins-Bessa, Ana; Quaresma, Miguel; Leiva, Belén; Calado, Ana; Arando, Ander; Marín, Carmen; Navas, Francisco Javier
Abstract: In endangered donkey populations, reproductive performance is one the most important areas to study, provided its connection with conservation opportunities. Among reproductive traits, testicular dimensions, their relationship with body weight and seminal qualitative and quantitative parameters is particularly notable. The aim of the present study was to model the evolution of body weight, testicular length, width and height, volume and gonadosomatic index in Miranda donkeys using in vivo ultrasonography. Data on the aforementioned variables of 23 Miranda donkeys, from 4 to 259 months of age, were fitted to eleven linear and nonlinear models. Cubic function modelling reported the best-fitting properties for almost all variables, except for body weight (sigmoid curve model). Cubic model presented a higher ability to capture interindividual variability (Adj. R 2 from 0.795 to 0.922) for testicular height, width, length and volume measurements than the rest of fucntions tested. Bayesian information criterion (BIC) values suggest in vivo ultrasonography may be a rather efficient and accurate tool when predicting for the evolution of testicular volume or gonadosomatic index than three-dimensional testicular measurements. Highlights: Cubic functions efficiently model testicular dimensions, volume and composite indices evolution. Ultrasonography objectively, accurately and reproducibly determines testicular volume. Testicular asymmetry physiologically occurs to balance bilateral testicular activity.